1999
DOI: 10.1097/00001756-199909090-00009
|View full text |Cite
|
Sign up to set email alerts
|

Memory consolidation in human sleep depends on inhibition of glucocorticoid release

Abstract: Early sleep dominated by slow-wave sleep has been found to be particularly relevant for declarative memory formation via hippocampo-neocortical networks. Concurrently, early nocturnal sleep is characterized by an inhibition of glucocorticoid release from the adrenals. Here, we show in healthy humans that this inhibition serves to support declarative memory consolidation during sleep. Elevating plasma glucocorticoid concentration during early sleep by administration of cortisol impaired consolidation of paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 14 publications
7
81
2
2
Order By: Relevance
“…32 Conversely, the reduction of cortisol by intranasal insulin may enhance declarative memory formation. 33 In accordance with previous results in normal-weight subjects, 9,34 insulin treatment also improved mood as reflected by decreased scores of introversion and anxiousness and trends toward reduced depressiveness and anger, corroborating that obese men are sensitive to the improving effects of intranasal insulin on neuropsychological functions.…”
Section: Discussionsupporting
confidence: 90%
“…32 Conversely, the reduction of cortisol by intranasal insulin may enhance declarative memory formation. 33 In accordance with previous results in normal-weight subjects, 9,34 insulin treatment also improved mood as reflected by decreased scores of introversion and anxiousness and trends toward reduced depressiveness and anger, corroborating that obese men are sensitive to the improving effects of intranasal insulin on neuropsychological functions.…”
Section: Discussionsupporting
confidence: 90%
“…One earlier study in humans examined the interaction between sleep and MR blockade on declarative and spatial memory (Plihal and Born, 1999) and failed to find an effect of MR blockade. However, there are considerable differences between this earlier and our study.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy humans, only one study examined the interaction of sleep and MR blockade on consolidation of declarative memory and failed to find an effect of MR blockade (Plihal and Born, 1999). However, in patients with Addison's disease it was recently shown that MR are needed for encoding learned material (Tytherleigh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared with SWS or wakefulness, serotonin and norepinehrine are less available during REM sleep (Pace-Schott and Hobson, 2002), and moreover, cortisol levels are higher during late REM sleep than early SWS-rich sleep (Born and Fehm, 1998). Increasing cortisol levels during sleep blocks the improving effect of sleep on declarative memory consolidation (Plihal and Born, 1999;Wagner and Born, 2008).…”
Section: Discussionmentioning
confidence: 99%